Application of high resolution OCT to evaluate irregularity of Bowman's layer in asymmetric keratoconus. Issue 5 (24th August 2016) - Pahuja, Natasha; Shroff, Rushad; Pahanpate, Pratik; Francis, Mathew; Veeboy, Leio; Shetty, Rohit; Nuijts, Rudy M. M. A.; Sinha Roy, Abhijit
Abstract : Irregularity of the Bowman's layer (BL) in keratoconus (KC, sample size ( n ) = 28) and forme fruste keratoconus (FFKC, n = 18) eyes was evaluated. Subjects underwent high resolution OCT imaging (Bioptigen Inc., USA) and corneal tomography (Pentacam v1.20r41, OCULUS Optikgeräte GmbH, Germany). Anterior edge of the BL was segmented. A Bowman's roughness index (BRI) was defined as the sum of the enclosed areas between segmented edge and a smooth 3 rd order polynomial fit to the edge. BRI was compared with corneal aberrations, Keratoconus percentage index (KISA), Cone location magnitude index (CLMI) and Belin–Ambrosio enhanced ectasia display overall deviation index (BAD‐D). Area under the curve (AUC) was determined with logistic regression (LR). Mean BRI (×10 –3 ) was 2.12 mm 2, 1.81 mm 2 and 1.7 mm 2 in normal ( n = 26), FFKC and KC eyes, respectively ( p < 0.001). BAD‐D (0.79) and BRI (0.74) had the best AUC for FFKC. By combining BAD‐D and BRI, the AUC improved to 0.85 ( p = 0.01). For KC eyes, KISA (0.94), CLMI (0.88), BAD‐D (0.96) and aberrations had comparable AUC ( p > 0.05). However, LR with BRI and other indices didn't improve the AUC in KC eyes ( p > 0.05). BRI was significantly reduced in FFKC and KC eyes. It improved the detection of FFKC but not KC eyes. Abstract : In this study, a new index, named as the Bowman's Roughness Index (BRI), was derived from high resolution OCT images of the Bowman's layer of the human cornea. BRI was altered in keratoconus, a biomechanical degradation of the cornea. BRI improved the detection of suspect keratoconus, despite normal tomography in such eyes. In advanced keratoconus, inclusion of BRI did not result in significant diagnostic improvement over conventional tomography indices.